Managing enterprise data complexity using web services part 1 data services architecture. - Anand, Dr. Sriram
Business data is one of the most critical components of the IT porfolio of any enterprise. Most e-business applications are responsible for reading and writing business data in some form or other. Therefore, the efficient storage, retrieval and management of the data constitute a challenging problem in all organizations.